Upstream Supply Chain Performance Efficiency: Case Study of Creator Coffee Roaster in Yogyakarta - Humanika, Erasmus; Laily, Dona Wahyuning; Irianto, Heru (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
The Creator Coffee Roaster is a speciality coffee processing business based in Yogyakarta and has been established since 2012. The company focuses on producing roasted coffee beans of various types, including Robusta, Arabica, and house blends that are uniquely crafted by the company. The raw coffee beans are sourced from multiple coffee-producing regions in Indonesia, giving their products a diverse richness of flavour. As consumer interest in speciality coffee continues to grow, the demand for The Creator Coffee Roaster’s products has also increased steadily. This study evaluates the efficiency of the supply chain using the Data Envelopment Analysis (DEA) method, with input variables such as cash-to-cash cycle time and order fulfilment cycle time, and output variables such as delivery performance and order fulfilment. The analysis results show that farmers 2 and 4 achieved 100% efficiency, while farmers 1 and 3 were still inefficient, with scores of 57.1% and 66.7%, respectively. The novelty of this research lies in utilising DEA, which adopts input and output variables from the SCOR 12.0 method to provide a data-driven evaluation, helping speciality coffee roastery SMEs optimise their supply chain strategy. Based on these findings, it is recommended that specialty coffee SMEs establish partnerships with efficient farmers, provide improvement feedback to those who are less efficient, and adopt data-driven supply chain management to enhance competitiveness and business sustainability.